The Natural History of Man - Swanson Carl P (Prentice Hall Inc, 1973)
Through a Kaleidoscope, A New Course is Charted, Of Time and Variation, Of Change and Chance, Evolution as a Process, Emerging Humanity, The Uniqueness of Man, The Uniqueness of the Individual, Evolution Revisited, Through a Glass Darkly, Bibliography Notes, Index.